An Analysis of Epistemological Learning Barriers on Newton’s Law Material in Engineering Class - Antomi Saregar; Hani Mulyani; Yetri Yetri; Adyt Anugrah; Konstantinos Ravanis (Yayasan Keluarga Guru Mandiri, 2020)
Physics learning barriers have been studied quite a lot, one of which is epistemological learning barriers. This study aims to determine the epistemological learning barriers and what the percentage of epistemological learning barriers on Newton’s law material about motion in one of the engineering class at one of the vocational high school in Indonesia. Therefore, the researchers reported the results of research related to epistemological learning barriers. This research was qualitative descriptive research. The subjects of this research were 65 students with an age range of 14-15 years. The data was collected using tests and interviews, then analyzed using data reduction, data presentation, and conclusions. The data validity was determined using technical triangulation. The results of this research indicated that high epistemological barriers were found in two indicators, namely the incorrect calculation and the difficulty to determine the right calculation units on the Newton’s First, Second, and Third Laws with the percentages of 88.75%, 6.87%, and 98.45% respectively. The average percentage epistemological learning barriers on the Newton’s First Law was 61.7% within the moderate category and the average percentages of epistemological learning barriers on Newton’s Second and Third Laws were 70.61% and 76.50% within the high categories. Based on these results, it can be concluded that students had difficulty calculating and determining Newton’s Laws’ unit of calculation. It indicated that the students experience epistemological learning barriers with a high category.